Shadow State Analysis Of Collaborative Elite In Peat Restoration Program Management - Susanti, Delpi; Hastuti, Weni Puji; Handayani, Dini; Pauzi, Achmad; Dharma, Anton Budhi; Handayani, Desi; Sujianto, Sujianto; Yustina, Yustina; Asyari, Hasim; Tua, Harapan; Yuliani, Febri (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
Peat restoration is a government strategic program which is a top priority area, especially for Riau Province. Peat restoration is also one of the pilot projects that must be handled correctly, quickly and thoroughly so that it does not repeat the wounds of the disaster like 7 years ago. This is because, as the owner of the largest peatland in Sumatra, history has also been categorized as the biggest source of forest and land fires. It was suspected that the restoration of the peat was originally due to forest and peatland fires, so that the World Bank once estimated that the economic loss from the karhutla disaster reached Rp. 221 Trillion (Mileva et al. 2016). In accordance with Presidential Decree No. 1 of 2016, the government established the Peat Restoration Agency which is the leader in implementing peat restoration in Indonesia (Lebaran et al. 2016). It should be known that peat restoration is indeed designed within the framework of collaboration with many elites (representative groups that are considered capable), namely the Government, communities, NGOs and the private sector, which are the key elites for the implementation of peat restoration (collaborative governance). The elite approach strategy is the focus of this study by using collaborative governance theory as the main research framework. This study uses a qualitative method with a case study approach assisted by literature studies. Researchers found that there was a failure of peat restoration management strategy in Riau. The unclear status of the Regional Peat Restoration Team (TRGD) and the inactivity of the Riau Provincial Government in supporting the peat restoration agenda became the findings of this study. Researchers see there are several factors that cause it to happen. Economic factors become the main ones because peat restoration is related to investments in forestry and oil palm plantations. Then the cause of the failure of the management strategy, namely failure to understand communication between elites, was also caused by a lack of commitment from elite leaders in Riau.